tìm x biết:
- (2x-1)^2=1/4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
PT \(\Rightarrow2x^2+2x-3x-6=2x^2-x+4x-8-2\)
\(\Rightarrow-4x=-4\) \(\Leftrightarrow x=1\)
Vậy \(x=1\)
Ta có: \(2x\left(x+1\right)-3\left(x+2\right)=x\left(2x-1\right)+4\left(x-2\right)-2\)
\(\Leftrightarrow2x^2+2x-3x-6=2x^2-x+4x-8-2\)
\(\Leftrightarrow2x^2-x-6=2x^2+3x-10\)
\(\Leftrightarrow2x^2-x-6-2x^2-3x+10=0\)
\(\Leftrightarrow-4x+4=0\)
\(\Leftrightarrow-4x=-4\)
hay x=1
Vậy: x=1
a) \(\dfrac{x}{3}=\dfrac{4}{12}\Rightarrow x=\dfrac{4}{12}\cdot3=\dfrac{12}{12}=1\)
b) \(\dfrac{x-1}{x-2}=\dfrac{3}{5}\) (Điều kiện : \(x\ne2\))
\(\Rightarrow5\left(x-1\right)=3\left(x-2\right)\)
\(\Leftrightarrow5x-5=3x-6\Leftrightarrow5x-3x=-6+5\Leftrightarrow2x=-1\Leftrightarrow x=-\dfrac{1}{2}\)
c) \(2x:6=\dfrac{1}{4}\Leftrightarrow2x=\dfrac{1}{4}\cdot6=\dfrac{6}{4}=\dfrac{3}{2}\Leftrightarrow x=\dfrac{3}{2}:2=\dfrac{3}{2}\cdot\dfrac{1}{2}=\dfrac{3}{4}\)
d) \(\dfrac{x^2+x}{2x^2+1}=\dfrac{1}{2}\)
\(\Rightarrow2\left(x^2+x\right)=2x^2+1\)
\(\Leftrightarrow2x^2+2x=2x^2+1\)
\(\Leftrightarrow2x^2+2x-2x^2=1\Leftrightarrow2x=1\Leftrightarrow x=\dfrac{1}{2}\).
(x+2)(x^2-2x+4)-x(x-1)(x+1)+2x=2
<=> x3 - 2x2 + 4x + 2x2 - 4x + 8 - x(x2 - 1) + 2x = 2
<=> x3 + 8 - x3 + x + 2x = 2
<=> 3x + 8 = 2
<=> x = -2
1) =>2x+4+4+x=11
=>2x+4+4+x-11=0
=>3x-3=0
=>3x=3
=> x=1
Vậy x thuộc {1}
2)=>x+x+1+2x+4=3
=>x+x+1+2x+4-3=0
=>4x+2=0
=>4x=-2
=>x=-2/4
=>x=-1/2
Vậy x thuộc {-1/2}
\(a,\Leftrightarrow x^3-8-x\left(x^2-9\right)=1\\ \Leftrightarrow x^3-8-x^3+9x=1\\ \Leftrightarrow9x=9\Leftrightarrow x=1\\ b,\Leftrightarrow8x^3+12x^2+6x+1-8x^3 +12x^2-6x+1-24x^2+24x-1=0\Leftrightarrow1=0\Leftrightarrow x\in\varnothing\)
a) \(\Leftrightarrow x^3-8-x^3+9x=1\)
\(\Leftrightarrow9x=9\Leftrightarrow x=1\)
b) \(\Leftrightarrow8x^3+12x^2+6x+1-8x^3+12x^2-6x+1-24x^2+24x-6=5\)
\(\Leftrightarrow24x=9\Leftrightarrow x=\dfrac{3}{8}\)
(2x-1)^2=1/4
x=3/4
cảm ơn